SISTEM NOTIFIKASI ANTRIAN BERBASIS ANDROID - Asep saefullah; Diah Ariyani; Andy Rienauld (Universitas Raharja, 2014)
An age of fast-paced time is precious, be in a queue sequence is a loss. In addition to timeconsuming, the queue can also restrict other activities to do one. Likewise, when making payments at the checkout counter can be ascertained will be a queue, it needed a solution for IT ( Information Technology ) to overcome losses incurred during the waiting queue. This research is to design and create an application system that can give information about the running queue and facility reservation queue numbers to someone from anywhere via smartphones with the Android operating system. Research using the Android Developer Tools ( ADT ) Bundle suggested by the official Android developer site as a tool to help software developers build, test and debug Android applications. The design of applications using a smartphone galaxy s3 android hardware and language as a programming language as well as software eclipse helper program making. The result is a system application Queue Notifications on smartphones with Android OS, where users can take advantage of the waiting time by not waiting in line at the cash register or point of payment but the queue in the queuing system on a smartphone from anywhere while doing other activities .